Sharing clinical trial data. (20th January 2016) - Taichman, Darren B; Backus, Joyce; Baethge, Christopher; Bauchner, Howard; Leeuw, Peter W de; Drazen, Jeffrey M; Fletcher, John; Frizelle, Frank A; Groves, Trish; Haileamlak, Abraham; James, Astrid; Laine, Christine; et al.
Abstract : A proposal from the International Committee of Medical Journal Editors